Dictyota falklandica sp. nov. (Dictyotales, Phaeophyceae) from the Falkland Islands and southernmost South America. Issue 6 (2nd November 2019) - Küpper, Frithjof C.; Peters, Akira F.; Kytinou, Eleni; Asensi, Aldo O.; Vieira, Christophe; Macaya, Erasmo C.; De Clerck, Olivier
ABSTRACT: Surveys of the seaweed flora of the Falkland Islands and of Tierra del Fuego revealed the presence of a new species of brown alga. Dictyota falklandica sp. nov . inhabits the shallow rocky infralittoral in sheltered localities and the lower intertidal in more exposed sites. Dictyota falklandica has a regular to irregular habit of dichotomously branched blades, forming erect thalli composed of a single-layered cortex and medulla, with margins in the apical parts dotted with dormant apical cells. Sporangia occur in irregular groups or longitudinal lines on the thallus surface. Molecular phylogenies based on chloroplast psb A and rbc L and mitochondrial cox 1 sequences showed that the species from the Falkland Islands is sister to a clade formed by D. korowai, recently described from New Zealand and D. kunthii known from both the Pacific coast of South America and New Zealand. Temperature tolerance experiments, showing mortality at 25 °C but survival at 20 °C, confirm the cold-temperate affinity of this taxon. Its relationship to other cold-temperate Southern Hemisphere species is discussed, with its closest relatives living in regions with sea surface temperatures of at least 7–10 °C higher.